Social Media and Academic Performance: A Case Study of Shree Jana Model Secondary School, Birendranagar, Surkhet - Paudel, Balkrishna (NPRC Journal of Multidisciplinary Research, 2025)
This study examines the impact of social media on the academic performance of secondary-level students at Shree Jana Model Secondary School in Birendranagar, Surkhet, Nepal. Using a descriptive and exploratory research design, primary data was collected through questionnaires and interviews with 82 randomly selected students, supplemented by secondary data from books, journals, and academic articles. The findings reveal that 92.68% of respondents were aged 16–18, with equal gender representation. Facebook was the most used platform (46.34%), and 53.65% of students spent 3–5 hours daily on social media, primarily for chatting (39.03%) rather than academic purposes. A significant 69.51% reported negative impacts on their academic performance, including decreased CGPA (25.60%), late assignment submissions (21.95%), and reduced study focus (9.75%). The study concludes that excessive social media usage adversely affects students' academic outcomes, highlighting the need for institutional policies and awareness programs to promote balanced usage and minimize distractions while leveraging social media as a constructive educational tool.